2016 International Conference on Information Management and Technology (ICIMTech) 2016
DOI: 10.1109/icimtech.2016.7930297
|View full text |Cite
|
Sign up to set email alerts
|

Integrating IS Success Model, SERVQUAL and Kano Model into QFD to improve Hospital Information System quality

Abstract: Hospital Information System (HIS) has become an important part of every healthcare institution in providing high quality clinical care and efficient daily operation. The purpose of this research is to evaluate the quality of HIS in a private multispecialty hospital in Indonesia as the mean to recommend possible actions for the management and IT department in the effort of achieving continuous improvements. The approach involves integrating SERVQUAL method, Kano Model and Quality Function Deployment (QFD) for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The optimal strategy is the campaign, recruitment of skilled human resources, performance measurement, and monitoring (Lee et al, 2015) Coupled fuzzy logic with QFD in healthcare services enables medical practitioners to understand customer requirements and include them for continuous improvement during the health service delivery 12 (Ionica & Leba, 2015) QFD method can be implemented in the innovative product NPD approach to produce innovative products by achieving customer satisfaction requirements 13 (Hashemi et al, 2015) The QFD used showed that the time spent on prescribing medication had been reduced by more than 20 percent. 14 (Nordin, 2015) The satisfaction coefficient is used to formulate optimization outputs for new and better health services 15 (Sandelands, 2015) The fuzzy QFD approach can provide a framework for analyzing technical requirements that can lead to the synthesis of a customer-oriented system 16 (Wibawa et al, 2016) Choose the best priority of improvement measures to increase user satisfaction. 17 (Wood et al, 2016) QFD has been applied in the construction industry with a special focus on supporting green hospital design 18 (Pourmadadkar et al, 2017) Prioritization of improvement in treatment for cardiovascular disease (CVD).…”
Section: Resultsmentioning
confidence: 99%
“…The optimal strategy is the campaign, recruitment of skilled human resources, performance measurement, and monitoring (Lee et al, 2015) Coupled fuzzy logic with QFD in healthcare services enables medical practitioners to understand customer requirements and include them for continuous improvement during the health service delivery 12 (Ionica & Leba, 2015) QFD method can be implemented in the innovative product NPD approach to produce innovative products by achieving customer satisfaction requirements 13 (Hashemi et al, 2015) The QFD used showed that the time spent on prescribing medication had been reduced by more than 20 percent. 14 (Nordin, 2015) The satisfaction coefficient is used to formulate optimization outputs for new and better health services 15 (Sandelands, 2015) The fuzzy QFD approach can provide a framework for analyzing technical requirements that can lead to the synthesis of a customer-oriented system 16 (Wibawa et al, 2016) Choose the best priority of improvement measures to increase user satisfaction. 17 (Wood et al, 2016) QFD has been applied in the construction industry with a special focus on supporting green hospital design 18 (Pourmadadkar et al, 2017) Prioritization of improvement in treatment for cardiovascular disease (CVD).…”
Section: Resultsmentioning
confidence: 99%
“…Although the gap score of tangibility is less than other dimensions in the present study, the users significantly are dissatisfied with tangibility of HIS. Wibawa et al (28) applied the SERVQUAL to evaluate a HIS in Indonesia. The system reliability and response time in their study had the highest gap score.…”
Section: Discussionmentioning
confidence: 99%
“…Sandelands (2015) [18] The fuzzy QFD approach can provide a framework for analyzing technical requirements that can lead to the synthesis of a customer-oriented system. Wibawa (2016) [19] Choose the best priority of improvement measures to increase user satisfaction. Wood et al (2016) [20] QFD has been applied in the construction industry with a special focus on supporting green hospital design.…”
Section: No Paper Identity Findingsmentioning
confidence: 99%